The results of integration measurements of indoor radon activity concentration in houses in Ružomberok town (Northern Slovakia) - SMETANOVÁ, Iveta; MÜLLEROVÁ, Monika; HOLÝ, Karol; MORAVCSÍK, Attila; KOVÁCS, Tibor; CSORDÁS, Anita; NEZNAL, Martin; NEZNAL, Matej; KOZAK, Krzysztof; MAZUR, Jadwiga; GRZADZIEL, Dominik (Contributions to Geophysics and Geodesy, 2015)
Integration measurements of indoor radon in houses were performed within the framework of the project “Harmonization of determining the radiation dose of the population originating from radon in V4 countries”. In Slovakia, the survey was performed in three localities: Záhorská Bystrica, Mochovce and Ružomberok. Monitoring started in March 2012 and lasted for one year. In Ružomberok ten houses were selected for monitoring purposes. The houses built before 1990 were predominantly chosen for the investigation. In selected houses in Ružomberok, radon activity concentration rarely exceeded 400 Bq/m3 in a three month period, in this case the inhabitants were advised how to lower radon exposure. No house was found with an annual radon activity concentration of more than 400 Bq/m3.